2006
DOI: 10.1103/physreva.74.052702
|View full text |Cite
|
Sign up to set email alerts
|

Double photoionization of aligned molecular hydrogen

Abstract: We present converged, completely ab initio calculations of the triple differential cross sections for double photoionization of aligned H2 molecules for a photon energy of 75.0 eV. The method of exterior complex scaling, implemented with both the discrete variable representation and B-splines, is used to solve the Schrödinger equation for a correlated continuum wave function corresponding to a single photon having been absorbed by a correlated initial state. Results for a fixed internuclear distance are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
150
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(161 citation statements)
references
References 39 publications
11
150
0
Order By: Relevance
“…The method has been successful in providing essentially exact results for both electron-impact ionization of atomic hydrogen [33] and double photoionization of atomic [25] and molecular two-electron targets [27][28][29]. Here we present the main broad strokes that illustrate how ECS successfully deals with problems invovling more than one continuum electron.…”
Section: Theoretical Framework a Exterior Complex Scaling Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The method has been successful in providing essentially exact results for both electron-impact ionization of atomic hydrogen [33] and double photoionization of atomic [25] and molecular two-electron targets [27][28][29]. Here we present the main broad strokes that illustrate how ECS successfully deals with problems invovling more than one continuum electron.…”
Section: Theoretical Framework a Exterior Complex Scaling Approachmentioning
confidence: 99%
“…Following the prescription for practical calculation of the double photoionization amplitude utilized for both atomic helium [25] and molecular hydrogen [29], we seek to decompose the full scattered wave into angular components on a radial grid in order to implement exterior complex scaling. Thus, the scattered wave function that solves Eq.…”
Section: B Formulation Of the Atomic Double Photoionization Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed that this essentially classical interpretation of nuclear motion (consistent with the "reflection principle" for photodissociation spectra) is valid for the conditions of the experiment. Recent theoretical work has reported the first complete numerical solution of the Schrödinger equation for the double photoionization of H 2 [25,47,[74][75][76]. The results have shown that the distribution of photoelectrons emitted from aligned molecules reflects electron correlation effects that are purely molecular in origin.…”
Section: Double Photoionization Of Hmentioning
confidence: 99%
“…Why does the fully differential cross section rotate with changing internuclear distance? This cross section is a coherent sum of contributions to the double photoionization amplitude from the components of the polarization parallel (Σ u ) and perpendicular (Π u ) to the molecular axis [75]. As shown in [76], the parallel contribution has a minimum in the range of internuclear distances being sampled by the experiment, while the perpendicular one decreases monotonically as R increases.…”
Section: Double Photoionization Of Hmentioning
confidence: 99%